Bank Resilience Analysis: The Role of Regulation, Adaptive‎Assets, and Speed with Performance and Risk As A Mediation Variable - abiwodo; Subroto, Athor; Umanto (International Journal of Accounting and Economics Studies, 2025)
The determination of the questionnaire was carried out using the Simple Random Sampling method with a sample size are 100 people. The ‎sample criteria for respondents were leaders or equivalent to at least Assistant, Assistant Manager, Manager, Assistant Vice President (AVP), ‎Vice President (VP), and Senior Vice President (SVP). Measurement of indicator variables was carried out using a Likert scale from 1 to 5An ‎explanatory approach was employed in this study to examine the interplay and impact of exogenous and endogenous variables. SEM PLS was ‎employed to analyze the data. According to the test results, Regulation has a substantial impact on the performance of the company, whereas ‎Adaptive, Assets, and Speed do not. The only factors that have a significant impact on risk are Speed and Assets, suggesting that risk is more ‎influenced by internal factors. Company Performance and Risk both contribute to Bank Resilience, with Risk as the dominant factor. Indirectly, ‎Regulation affects Bank Resilience through Company Performance, while Assets and Speed through Risk. Thus, Company Performance and ‎Risk can be important mediators in strengthening bank resilience through certain internal factors‎.